“My Whole Life I’ve Been on the Run”: Fugitivity as a Postracial Trope in Red Dead Redemption 2 - Marks, Katrina (American Literature, 2022)
This article discusses the popular video game Red Dead Redemption 2 (2018) by Rockstar Games, which follows Arthur Morgan, a white outlaw, during the decline of the “Wild West” in 1898 and 1899. Taking up conversations of fugitivity in critical ethnic studies, this article maintains that fugitivity operates as a rhetorical trope that stands in for racial identity where the logic of postracialism denies investments in race. Analyzing the narrative, spatial, and kinesthetic elements of the game, this article argues that Morgan, and by extension the player, is aligned with historically and geographically racialized others through a fugitive relationship to space. While Rockstar, as a video game studio, may not see itself explicitly intervening in a racialized and racializing political imaginary in its fictional worldbuilding, the kinesthetic, narrative, and cartographic strategies the studio employs respond to a set of cultural assumptions rooted in the rhetoric of postracialism. As such, Red Dead Redemption 2 serves as a multifaceted text through which to interrogate the dynamics of that rhetoric as it is mobilized in representations of fugitivity and identity.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé